Characterization of laser cladding materials for rail steel repair - Teo, Kennedy Jie Yi (Nanyang Technological University, 2020)
Rail defects have the potential to disrupt the rail industry and possibly lead to disastrous events if the defective rails are not identified and replaced. Laser cladding repair of rail steel has shown promise as a viable solution. The aim of this research is to determine how laser cladding would affect the metallurgical properties of rail steel and to characterise the laser cladding material used. For this study, the cladding material selected is Stellite 6 due to its high hardness and strength. As defects were more likely to occur on curved tracks, the base material chosen is R350HT grade rail steel. Microscopic, microstructural and microhardness analysis were carried out to assess if the cladding material conforms with the rail substrate. Dendrite, martensite and pearlite phases were observed in the cladded, heat affected zone (HAZ) and the substrate regions, respectively. In addition, shear testing and analysis was conducted to check for possible delamination and to investigate the clad-rail substrate interface bond strength. All 4 specimens had obtained a higher shear strength as compared to the substrate material. Future research of the cladding material Inconel 718 on rail steel and the preventive aspect of maintenance instead of repairing aspect were proposed.